2023
DOI: 10.1021/acsomega.2c06451
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Lipopolysaccharide-Induced Inflammatory Responses through Inhibition of the NF-κB Pathway and the Increased NRF2 Level by a Flavonol-Enriched n-Butanol Fraction from Uvaria alba

Abstract: Pathologic hyperreactive inflammatory responses occur when there is excessive activation of a proinflammatory NF-κB pathway and a reduced cytoprotective NRF2 cascade. The noncytotoxic, highly selective COX-2 inhibitory flavonol-enriched butanol fraction (UaB) from Uvaria alba (U. alba) was investigated for its inflammatory modulating potential by targeting NF-κB activation and NRF2 activity. Enzyme-linked immunosorbent assay was initially performed to measure levels of proinflammatory mediators [nitric oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…By activating NF-kB and AP-1, inhibiting the inflammatory-causing activation of enzymes such as cyclooxygenase-2, lipoxygenase, and inducible NO synthase, and activating phase II antioxidant detoxifying enzymes in rats, flavonoids have been shown to have anti-inflammatory properties through molecular mechanisms 39 . Pro-inflammatory cytokines/chemokines are inhibited by antioxidants in a variety of cell types, such as peripheral blood mononuclear cells, Jurkat T-cells, and RAW macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…By activating NF-kB and AP-1, inhibiting the inflammatory-causing activation of enzymes such as cyclooxygenase-2, lipoxygenase, and inducible NO synthase, and activating phase II antioxidant detoxifying enzymes in rats, flavonoids have been shown to have anti-inflammatory properties through molecular mechanisms 39 . Pro-inflammatory cytokines/chemokines are inhibited by antioxidants in a variety of cell types, such as peripheral blood mononuclear cells, Jurkat T-cells, and RAW macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
“…Bilobalide, ginkgolide A, and so on can play an anti‐inflammatory role by regulating inflammation‐related pathways and inhibiting the release of inflammatory factors. Quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, and isorhamnetin‐3‐O‐rutinoside can inhibit the PI3K‐Akt, NF‐κB, and other signalling pathways and reduce cardiovascular and cerebrovascular injuries 37–44 . The ingredients such as caffeic acid, protocatechuic acid, gallic acid, bilobalide, ginkgolide A, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, and isorhamnetin‐3‐O‐rutinoside also have anti‐oxidative, free radical‐scavenging, and anti‐apoptotic effects 22–50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations